Das Verhältnis von Selbstbestimmungsaufklärung und therapeutischer Aufklärung - Holland, Dario (Universitätsverlag Göttingen, 2017)
In addition to the risk of treatment failure, the liability for elucidation errors forms the second pillar of medical care. An elucidation error occurs when the physician has not given the patient the necessary self-determination information. The self-determination investigation is intended to enable the patient to decide on his own responsibility whether he wants to undergo a specific procedure. The consent of the patient to a medical procedure is only effective if he has received a proper self-determination information beforehand. The doctor must prove that the patient has received a proper self-determination. Self-determination elucidation must be distinguished from the therapeutic elucidation. The therapeutic elucidation aims to avoid self-harming the patient and to lead him a therapy-friendly behavior. Therapeutic elucidation is assigned to the area of medical treatment, with all the consequences of evidence. Thus, inadequate or omitted therapeutic elucidation represents a treatment defect, which must in principle be proven by the patient. Against this background, the relationship between self-determination elucidation and therapeutic elucidation is becoming increasingly important.